Inspiratory muscle training for people with Parkinson’s disease: a protocol for a mixed methods randomised controlled trial - Bernie Bissett; Juliana Fernandes Barreto de Mendonca; Elisabeth Preston; Allyson Flynn (BMJ Open Respiratory Research, 2025)
Introduction Inspiratory muscle weakness is a known consequence of Parkinson’s disease and could be a potential contributor to the dyspnoea experienced by many people living with the condition. Inspiratory muscle training is effective in improving inspiratory muscle strength and reducing dyspnoea in other chronic diseases. However, inspiratory muscle training has received little attention in people with Parkinson’s disease, and it is unclear how this training affects inspiratory muscle strength, dyspnoea and quality of life.Methods and analysis This mixed methods, randomised controlled trial will recruit 50 participants with idiopathic Parkinson’s disease who will be randomly allocated to either the experimental group, for 8 weeks, or the control group. Inspiratory muscle strength (maximum inspiratory pressure) will be the primary outcome. The secondary outcomes include motor experience of daily living (Movement Disorder Society-Unified Parkinson’s Disease Rating Scale part II), rate of perceived exertion (modified Borg Scale), exercise capacity (6-minute walk test) and quality of life (39-item Parkinson’s Disease Questionnaire). Quantitative data will be analysed using descriptive statistics. Semi-structured interviews will be conducted with participants who underwent inspiratory muscle training. Inductive reflexive thematic analysis will be used to explore the participants’ experiences of inspiratory muscle training and its impact on dyspnoea, activities of daily living and overall quality of life.Trial registration number ACTRN12622000097741.